The 'gap' in the 'plasma osmolar gap'. (8th August 2013) - Arora, Alok
Abstract : Ethylene glycol poisoning is a medical emergency that presents challenges for clinicians and clinical laboratories. If left untreated, it may cause morbidity and death, but effective therapy is available if diagnosed in time. The diagnosis of ethylene glycol poisoning is not always straightforward and the commonly quoted 'plasma osmolar gap' is not sufficiently sensitive to exclude a small ingestion and has been reported to be normal in a number of serious exposures. The 'plasma osmolar gap' cannot distinguish among ethanol, isopropyl alcohol, methanol or ethylene glycol. Thus, the measurement of serum ethylene glycol and, ideally, glycolic acid, its major toxic metabolite in serum, is definitive. This also holds true for methanol and its metabolite formic acid. Ethylene glycol metabolites target the kidney and lead to reversible oliguric or anuric injury, which in turn slows the elimination of ethylene glycol. The therapeutic options include reversal of metabolic acidosis, inhibition of alcohol dehydrogenase and early haemodialysis.